1989
DOI: 10.1104/pp.91.4.1625
|View full text |Cite
|
Sign up to set email alerts
|

Water Transport in the Liana Bauhinia fassoglensis (Fabaceae)

Abstract: To determine the efficiency of xylem conductance in the liana (woody vine) Bauhinia fassoglensis Kotschy ex Schweinf., we measured hydraulic conductance per unit stem length (measured Kh), leaf-specific conductivity (LSC = Kh/distal leaf area), transpiration rate (E), xylem water potential (I), vessel number, and vessel diameter. The measured Kh was 49% (SE = 7%) of the predicted Kh from Poiseuille's law. The mean LSC for unbranched stem segments was 1.10 x 10-6 square meters per megapascal per second (SE = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 27 publications
2
40
0
Order By: Relevance
“…The values of measured Kh were on average only 14-26% of theoretically predicted Kh values based on Hagen-Poiseuille equation for ideal capillary. Similar results were found also in other studies (Ewers et al 1989, Martre et al 2000. There are three main factors that contribute to this discrepancy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The values of measured Kh were on average only 14-26% of theoretically predicted Kh values based on Hagen-Poiseuille equation for ideal capillary. Similar results were found also in other studies (Ewers et al 1989, Martre et al 2000. There are three main factors that contribute to this discrepancy.…”
Section: Discussionsupporting
confidence: 92%
“…Leaf specific conductivity was determined as the ratio between measured Kh and leaf area distal from the segment (Ewers et al 1989). Huber value was calculated as ratio of conducting xylem area per supported leaf area (Tyree and Ewers 1991).…”
Section: Methodsmentioning
confidence: 99%
“…2), higher conductivities being associated with larger vessel diameters. This association is already well documented (Zimmermann, 1983 ;Calkin et al, 1985 ;Ewers et al, 1989) and is attributed to the Hagen-Poiseuille equation whereby conductance is related to the fourth power of the conduit radius (Zimmermann, 1983). The pattern of the response of hydraulic conductivites to environmental conditions seems to vary between species.…”
Section: mentioning
confidence: 59%
“…Note the log scale of the y axis. Huber values increase exponentially from roots to stems ( Ewers et al (1989), and are based on leaf-specific conductivities (LSC) shown in Fig. 3.…”
Section: Vessel Diameter and Lengthmentioning
confidence: 99%